if condition problem and positive condition
1 visualización (últimos 30 días)
Mostrar comentarios más antiguos
Redwood
el 18 de Oct. de 2019
Comentada: Redwood
el 19 de Oct. de 2019
Dear Matlab experts,
I added "if condition" in the Matlab coding.
I defined m1 = n1-ee1, and I used "if condition" because I would like to get only positive value for m1.
However, I could not get any result.
if n1 <= ee1
m1 =0;
else if n1 > ee1
m1 = n1 - ee1;
My full coding is below. Please let me know how to fix it.
Thank you very much in advance.
Sincerely yours,
J1
t = 0:.0001: 5;
z = 1819;
e1 = -42;
e2 = -7;
e3= -20;
e4= -29;
e5 = -32;
e6 = -112;
e7 = -70;
e8 = -9;
e9 = -48;
e10 = -14;
e11 = -2;
e12 = -22;
e13= -42;
e14= -15;
e15 = -26;
e16 = -58;
e17 = -24;
e18 = -73;
e19 = -102;
e20 = -78;
e21 = -600;
e22 = -11;
e23= -65;
e24= -285;
e25 = -32;
p = exp(-t.*e1) + exp(-t.*e2) + exp(-t.*e3) + exp(-t.*e4) + exp(-t.*e5) + exp(-t.*e6) + exp(-t.*e7) + exp(-t.*e8) + exp(-t.*e9) + exp(-t.*e10) + exp(-t.*e11) + exp(-t.*e12) + exp(-t.*e13) + exp(-t.*e14) + exp(-t.*e15) + exp(-t.*e16) + exp(-t.*e17) + exp(-t.*e18) + exp(-t.*e19) + exp(-t.*e20) + exp(-t.*e21) + exp(-t.*e22) + exp(-t.*e23) + exp(-t.*e24) + exp(-t.*e25) ;
b1 = (exp(-t.*e1))./p;
b2 = (exp(-t.*e2))./p;
b3 = (exp(-t.*e3))./p;
b4 = (exp(-t.*e4))./p;
b5 = (exp(-t.*e5))./p;
b6 = (exp(-t.*e6))./p;
b7 = (exp(-t.*e7))./p;
b8 = (exp(-t.*e8))./p;
b9 = (exp(-t.*e9))./p;
b10 = (exp(-t.*e10))./p;
b11 = (exp(-t.*e11))./p;
b12 = (exp(-t.*e12))./p;
b13 = (exp(-t.*e13))./p;
b14 = (exp(-t.*e14))./p;
b15 = (exp(-t.*e15))./p;
b16 = (exp(-t.*e16))./p;
b17 = (exp(-t.*e17))./p;
b18 = (exp(-t.*e18))./p;
b19 = (exp(-t.*e19))./p;
b20 = (exp(-t.*e20))./p;
b21 = (exp(-t.*e21))./p;
b22 = (exp(-t.*e22))./p;
b23 = (exp(-t.*e23))./p;
b24 = (exp(-t.*e24))./p;
b25 = (exp(-t.*e25))./p;
n1 = z*b1;
n2 = z*b2;
n3 = z*b3;
n4 = z*b4;
n5 = z*b5;
n6 = z*b6;
n7 = z*b7;
n8 = z*b8;
n9 = z*b9;
n10 = z*b10;
n11 = z*b11;
n12 = z*b12;
n13 = z*b13;
n14 = z*b14;
n15 = z*b15;
n16 = z*b16;
n17 = z*b17;
n18 = z*b18;
n19 = z*b19;
n20 = z*b20;
n21 = z*b21;
n22 = z*b22;
n23 = z*b23;
n24 = z*b24;
n25 = z*b25;
ee1 = 42;
ee2 = 7;
ee3 = 20;
ee4 = 29;
ee5 = 32;
ee6 = 112;
ee7 = 70;
ee8 = 9;
ee9 = 48;
ee10 = 14;
ee11 = 2;
ee12 = 22;
ee13 = 42;
ee14 = 15;
ee15 = 26;
ee16 = 58;
ee17 = 24;
ee18 = 73;
ee19 = 102;
ee20 = 78;
ee21 = 600;
ee22 = 11;
ee23 = 65;
ee24 = 285;
ee25 = 32;
m1 = n1 - ee1;
m2 = n2 - ee2;
m3 = n3 - ee3;
m4 = n4 - ee4;
m5 = n5 - ee5;
m6 = n6 - ee6;
m7 = n7 - ee7;
m8 = n8 - ee8;
m9 = n9 - ee9;
m10 = n10 - ee10;
m11 = n11 - ee11;
m12 = n12 - ee12;
m13 = n13 - ee13;
m14 = n14 - ee14;
m15 = n15 - ee15;
m16 = n16 - ee16;
m17 = n17 - ee17;
m18 = n18 - ee18;
m19 = n19 - ee19;
m20 = n20 - ee20;
m21 = n21 - ee21;
m22 = n22 - ee22;
m23 = n23 - ee23;
m24 = n24 - ee24;
m25 = n25 - ee25;
if n1 <= ee1
m1 =0;
else if n1 > ee1
m1 = n1 - ee1;
y = m1.*m1 + m2.*m2 + m3.*m3 + m4.*m4 + m5.*m5 + m6.*m6 + m7.*m7 + m8.*m8+ m9.*m9 + m10.*m10 +m11.*m11 + m12.*m12 + m13.*m13 + m14.*m14 + m15.*m15 + m16.*m16 + m17.*m17 + m18.*m18+ m19.*m19 + m20.*m20+ m21.*m21 + m22.*m22 + m23.*m23 + m24.*m24 + m25.*m25;
plot(t, sqrt(y))
[ymin, yi] = min(y);
tmin = t(yi)
ymin =y(yi)
0 comentarios
Respuesta aceptada
Image Analyst
el 19 de Oct. de 2019
You separated the else and the if. It should be elseif (one word) but actually you don't even need it. Try this:
if n1 <= ee1
m1 = 0;
else
m1 = n1 - ee1;
end
Más respuestas (0)
Ver también
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!